2015
DOI: 10.4278/ajhp.140128-quan-49
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity and Sedentary Behaviors in Explaining the Association between Acculturation and Obesity among Mexican-American Adults

Abstract: Purpose We investigated associations of acculturation with various types of activity (moderate-vigorous leisure-time physical activity (LTPA), moderate-vigorous work- and transportation-related physical activity and sedentary activity), and whether these activities mediated the acculturation-obesity association among Mexican-Americans. Design Cross-sectional. Setting National Health and Nutrition Examination Surveys 2007–2010. Subjects Mexican-American NHANES participants aged ≥ 20 years (n=1,902). Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
4
38
1
1
Order By: Relevance
“…Another NHANES study showed that US-born Mexican Americans engaged in more minutes per week of leisure time physical activity relative to Mexican-born counterparts. However, US-born individuals were also more likely to report having done no work or travel-related physical activity and therefore reported fewer minutes of total physical activity [ 40 ]. For children, analysis of the US National Survey of Children’s Health showed that migrant children were substantially less likely than native-born children to engage in sports and physical activity [ 5 ] which was reflected in analysis of the Canadian Health Behaviour in School-Aged Children Study [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another NHANES study showed that US-born Mexican Americans engaged in more minutes per week of leisure time physical activity relative to Mexican-born counterparts. However, US-born individuals were also more likely to report having done no work or travel-related physical activity and therefore reported fewer minutes of total physical activity [ 40 ]. For children, analysis of the US National Survey of Children’s Health showed that migrant children were substantially less likely than native-born children to engage in sports and physical activity [ 5 ] which was reflected in analysis of the Canadian Health Behaviour in School-Aged Children Study [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The foreign-born are less likely to meet overall physical activity recommendations than the US-born, but also to have less sedentary behavior. 8,16-18 US birth and longer US residence have also been associated with higher prevalence of diabetes, hypercholesterolemia, and hypertension, but the presence and strength of these associations varies across studies. 19-22 If residence in the US contributes to accelerated progression of overall cardiovascular risk, interventions targeted to recent immigrants may be an effective way to reduce future cardiovascular disease burden in immigrant populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the focus of study was not acculturation, the significant ethnic and sex differences in physical activity and BMI persisted even after adjustment for nativity and level of English‐language proficiency. Studies investigating the influence of acculturation on physical activity in Hispanics of all ages generally find that acculturation is negatively associated with healthy diet and physical activity, although other studies have mixed results . Most of this research has focused on early and middle adulthood, and as such, there is a paucity of studies examining these associations in older Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the influence of acculturation on physical activity in Hispanics of all ages generally find that acculturation is negatively associated with healthy diet and physical activity, although other studies have mixed results. 31 Most of this research has focused on early and middle adulthood, and as such, there is a paucity of studies examining these associations in older Hispanics. It is possible that these inconclusive results are due to methodology and acculturation measurement issues.…”
Section: Discussionmentioning
confidence: 99%